Estructura del tipo objetivo en los delitos de mera actividad, perspectiva ex ante. - Clerquer, Sofía G. (2022)
The present investigative study entitled "Structure of the objective type in crimes of mere activity, ex ante perspective", proposes to analyze some crimes of mere activity in its ex ante perspective, when they have the elements of the objective type and the unjust to be sanctioned. The fundamental idea is to carry out a dogmatic - criminal legal analysis of the normative, doctrinal framework, considering if the ex ante perspective fits in this type of crime and to make a brief reference to the general structure of the unjust, which is determined according to the function that it fulfills. the legal-criminal norm. This seeks to achieve an effect on the behavior of its recipient, in the sense of avoiding the production of a certain state of affairs or achieving the production of any behavior. The penalty established by the legislator in the legal statement does not only represent the definition of the punishment of the crime of mere activity, but also the means to influence the addressee of the norm. Thus, this class of crimes, by not having a total structure of the objective type and by not having a final result, should not be criminally relevant behaviors or be treated as a crime merely said, the proposal is to change to an infraction as a contravention and that they be sanctioned with a proportion of the damage caused, that is, with a pecuniary penalty but not with a custodial sentence.